Short- and Long-Term Exercise Results in a Differential Achilles Tendon Mechanical Response - Chen, Mengcun (J Biomech Eng, 2020)
The study was conducted to define the biomechanical response of rat Achilles tendon after a single bout of exercise and a short or long duration of daily exercise. We hypothesized that a single bout or a short duration of exercise would cause a transient decrease in Achilles tendon mechanical properties and a long duration of daily exercise would improve these properties. One hundred and thirty-six Sprague-Dawley rats were divided into cage activity (CA) or exercise (EX) groups for a single bout, short-term, or long-term exercise. Animals in single bout EX groups were euthanized, 3, 12, 24, or 48 h upon completion of a single bout of exercise (10 m/min, 1 h) on a flat treadmill. Animals in short-term EX groups ran on a flat treadmill for 3 days, 1, or 2 weeks while animals in long-term EX groups ran for 8 weeks. Tendon quasi-static and viscoelastic response was evaluated for all Achilles tendons. A single bout of exercise increased tendon stiffness after 48 h of recovery. Short-term exercise up to 1 week decreased cross-sectional area, stiffness, modulus, and dynamic modulus of the Achilles tendon. In contrast, 8 weeks of daily exercise increased stiffness, modulus, and dynamic modulus of the tendon. This study highlights the response of Achilles tendons to single and sustained bouts of exercise. Adequate time intervals are important to allow for tendon adaptations when initiating a new training regimen and overall beneficial effects to the Achilles tendon.